An all-process neutral color conversion electrochromic device and a preparation method thereof
Patent Information
- Application Number
- CN202611167400.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-27
AI Technical Summary
[0016]有益效果:与现有技术相比,本发明提供的一种基于MxWyMozO3薄膜的全过程中性色转变电致变色器件,通过磁控溅射方法成功制备得到所述薄膜,工艺简单成本低。通过调控材料在不同波段的吸收能力,拓宽材料的光学吸收范围至全可见光波段,制备得到的电致变色薄膜可以实现变色过程中的全过程中性色转变,满足人眼舒适度对于中性色的需求。通过与透明导电层和不具备电致变色活性的透明离子存储层串联成电致变色器件,不仅实现了完整电致变色器件在变色过程中的全过程中性色演变,还具有优异的循环稳定性,可应用于电致变色智能窗、可穿戴设备等领域。
Smart Images

Figure CN122984252A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochromic technology, and more particularly to an electrochromic device with a neutral color change throughout the process and its preparation method. Background Technology
[0002] Electrochromism refers to the phenomenon that certain materials undergo stable and reversible changes in their optical properties (reflectivity, transmittance, absorptivity, etc.) under an applied electric field. It can dynamically adjust light transmission and heat insulation, showing significant energy-saving potential in fields such as smart windows and smart wearable devices.
[0003] Currently, compared to organic electrochromic materials, inorganic metal oxide thin films have been a research hotspot in this field due to their relatively stable performance during ion interaction. However, the color changes of existing inorganic electrochromic materials are mostly limited to a single color (e.g., WO3 colored state is blue, NiO colored state is brown), exhibiting significant color bias. This makes it difficult to meet the architectural aesthetics and visual comfort requirements for "neutral colors" (e.g., transparent-gray-black), and also limits their application in fields such as anti-glare rearview mirrors and smart electronic sunglasses. Furthermore, the inability of electrochromic materials themselves to achieve neutral colors also affects the realization of neutral colors in complete electrochromic devices, further restricting the development of electrochromic technology. Therefore, constructing neutral colors to achieve full-band visible light modulation is of great significance for further expanding the application prospects of electrochromic materials.
[0004] In existing technologies, neutral colors are typically achieved through doping or organic molecular structure design, or by combining the performance of the counter electrode to create a device that achieves color complementarity. However, poor performance and cycling stability limit its large-scale application. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the purpose of this invention is to provide an electrochromic device with neutral color change throughout the entire process and its preparation method, aiming to solve the problems that existing electrochromic technologies are difficult to achieve neutral color change throughout the entire color change process and are difficult to meet the needs of practical application scenarios.
[0006] To address the above technical problems, in a first aspect, the present invention provides a method for preparing an electrochromic device with a neutral color change throughout the entire process, comprising the following steps: M was obtained by co-sputtering metals M, W, and Mo on the surface of the first ITO glass using magnetron sputtering. x W y Mo z O3 thin film, wherein M is selected from at least one of Nb and Ti; For the M x W y Mo zThe O3 thin film underwent a first annealing treatment to obtain amorphous M. x W y Mo z O3 cathode electrochromic layer; Metal oxides were co-sputtered onto the surface of a second ITO glass using magnetron sputtering, and the resulting film was subjected to a second annealing treatment to obtain a transparent anodic ion storage layer without electrochromic activity. The amorphous M x W y Mo z The O3 cathode electrochromic layer and the transparent anode ion storage layer are assembled with their thin film surfaces facing each other and their electrodes facing opposite directions, separated by a spacer. Injecting a transparent electrolyte into amorphous M x W y Mo z The gap between the O3 cathode electrochromic layer and the transparent anode ion storage layer is encapsulated to obtain the electrochromic device.
[0007] As a preferred technical solution, in the method for fabricating the electrochromic device, the vacuum degree of the vacuum chamber in the magnetron sputtering method is 10. -3 ~10 -5 Pa, the working gas is a mixture of oxygen and argon.
[0008] As a preferred technical solution, the method for fabricating the electrochromic device includes preparing amorphous M by magnetron sputtering. x W y Mo z O3 cathode electrochromic layer, wherein the power supply of the metal M target is 150 W to 250 W, the power supply of the metal W target is 20 W to 60 W, and the power supply of the metal Mo target is 20 W to 120 W. Preferably, the annealing temperature of the first annealing treatment is 350℃~400℃, and the annealing time is 60 min~120 min.
[0009] As a preferred technical solution, in the method for preparing the electrochromic device, wherein the M x W y Mo z In the O3 thin film, x takes values of 0.5~0.6, y takes values of 0.2~0.3, and z takes values of 0.1~0.2; Preferably, the M x W y Mo z The thickness of the O3 thin film electrochromic film is 300~400nm.
[0010] As a preferred technical solution, in the method for preparing the electrochromic device, the material of the transparent anodic ion storage layer is Ce. a Ti b O film or M m V n O thin film; wherein M is selected from at least one of Nb and Ta.
[0011] As a preferred technical solution, in the method for preparing the electrochromic device, when the transparent anode ion storage layer is Ce... a Ti b When sputtering the O thin film, a Ce metal target and a Ti metal target are used for co-sputtering on the surface of the second ITO glass substrate; wherein, the power supply of the Ce metal target is 120 W to 200 W, and the power supply of the Ti metal target is 230 W to 240 W; the annealing temperature of the annealing treatment is 300℃ to 500℃, and the annealing time is 60 min to 120 min. Preferably, the Ce a Ti b The a value in the O thin film is 0.4~0.8 and the b value is 0.2~0.6.
[0012] As a preferred technical solution, in the method for preparing the electrochromic device, wherein the transparent anode ion storage layer is M m V n When sputtering the ITO thin film, a metal M target and a metal V target are used for co-sputtering on the surface of the ITO glass substrate; wherein, the power of the metal M target is 30 W to 45 W, and the power of the metal V target is 140 W to 160 W; the annealing temperature of the annealing treatment is 580-620℃, and the annealing time is 100-140 min. Preferably, the M m V n The m value in the O thin film is 0.4~0.6, and the n value is 0.4~0.6.
[0013] As a preferred technical solution, in the method for preparing the electrochromic device, the transparent electrolyte is obtained by mixing a lithium salt solution as the electrolyte with an ultraviolet-curable adhesive and stirring in the dark. The lithium salt in the lithium salt solution includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium bis(oxaloyl)borate, lithium tetrafluoroborate, lithium difluorooxaloylborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, and lithium tetrafluorooxaloyl phosphate.
[0014] As a preferred technical solution, in the method for preparing the electrochromic device, the solvent in the lithium salt solution includes at least one of propylene carbonate, ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl carbonate, and diethyl carbonate.
[0015] Secondly, an electrochromic device with a neutral color change throughout the process is provided, wherein it is prepared using the preparation method described above.
[0016] Beneficial effects: Compared with the prior art, the present invention provides a method based on M x W y Mo z An electrochromic device with full-process neutral color change of O3 thin film was successfully prepared by magnetron sputtering, a simple and low-cost process. By controlling the absorption capacity of the material in different wavelength bands, the optical absorption range of the material is broadened to the full visible light band. The prepared electrochromic film can achieve full-process neutral color change during the color-changing process, meeting the human eye's requirement for neutral color comfort. By connecting it in series with a transparent conductive layer and a transparent ion storage layer without electrochromic activity to form an electrochromic device, not only is a full-process neutral color evolution of the complete electrochromic device achieved, but it also has excellent cycle stability, and can be applied in electrochromic smart windows, wearable devices, and other fields. Attached Figure Description
[0017] Figure 1 Nb prepared in Example 1 0.55 W 0.3 Mo 0.15 The optical transmittance of O3 thin film in the visible light band changes under different voltages during the electrochromic process.
[0018] Figure 2 The cubic Ce phase prepared in Example 1 0.7 Ti 0.3 Optical transmittance spectra of O thin films in the transparent state and in the visible light band after applying a bias voltage.
[0019] Figure 3 The graph shows the change in optical transmittance of the device prepared in Example 1 in the visible light band under different voltages during the electrochromic process.
[0020] Figure 4 The graph shows the change in single-wavelength optical transmittance at 550 nm for the device prepared in Example 1 under constant voltage cycling test.
[0021] Figure 5 Three-dimensional CIE L of the device prepared in Example 1 during the color-changing process. a b Color coordinate variation graph. Detailed Implementation
[0022] This invention provides a method for preparing an electrochromic device with neutral color change throughout the process, comprising the following steps: S101, using magnetron sputtering, metals M, W, and Mo are co-sputtered onto the surface of the first ITO glass to obtain M. x W y Mo z O3 thin film, wherein M is selected from at least one of Nb and Ti; S102, regarding the M x W y Mo z The O3 thin film underwent a first annealing treatment to obtain amorphous M. x W y Mo z O3 cathode electrochromic layer; S103. A metal oxide is co-sputtered onto the surface of a second ITO glass using magnetron sputtering, and the resulting film is subjected to a second annealing treatment to obtain a transparent anodic ion storage layer without electrochromic activity. S104, the amorphous M x W y Mo z The O3 cathode electrochromic layer and the transparent anode ion storage layer are assembled with their thin film surfaces facing each other and their electrodes facing opposite directions, separated by a spacer. S105, Injecting a transparent electrolyte into amorphous M x W y Mo z The gap between the O3 cathode electrochromic layer and the transparent anode ion storage layer is encapsulated to obtain the electrochromic device.
[0023] This invention achieves dynamic control of the cathode amorphous M x W y Mo z The relative proportions of the three metal elements M (Nb or Ti), W, and Mo in the O3 ternary metal oxide thin film are altered to change the optical absorption capacity of the material in different wavelength regions of visible light. This enables it to achieve uniform and smooth optical modulation characteristics across the entire visible light spectrum (400 nm to 800 nm), thereby exhibiting a continuous, color-biased neutral color transition effect from a transparent state to a gray state and then to a black state during the electrochromic process.
[0024] Meanwhile, a transparent metal oxide film that does not possess electrochromic activity (i.e., does not undergo a color change perceptible to the naked eye under an applied voltage) is selected as the anode ion storage layer and paired with the cathode electrochromic layer to assemble the device. This fundamentally avoids the color interference and kinetic mismatch problems introduced by the participation of the electrode itself in color change in traditional color complementary strategies. Since the anode ion storage layer remains highly transparent throughout the entire color-changing cycle, the visual color change of the device is entirely controlled by the single variable of the cathode electrochromic layer, and the neutral color characteristics of the cathode electrochromic layer itself ensure that the device as a whole exhibits a stable and continuous neutral color evolution effect throughout the entire color-changing process.
[0025] Furthermore, the "amorphous M" constructed in this invention x W y Mo z The tandem device structure of "O3 cathode electrochromic layer / transparent electrolyte / non-electrochromic active transparent anode ion storage layer" not only achieves color evolution throughout the process but also exhibits excellent cycle stability. On the one hand, the amorphous structure of M x W y Mo z The O3 thin film provides isotropic diffusion channels for lithium-ion insertion and extraction, reducing capacity decay caused by lattice distortion during cycling. On the other hand, the anodic ion storage layer, which lacks electrochromic activity, only performs ion storage and release functions and does not participate in redox color-changing reactions. Therefore, its microstructure remains highly stable during cycling and is not prone to performance degradation. The synergistic effect of these two elements ensures the overall performance stability of the device during long-term cycling.
[0026] In one implementation of the present invention, the magnetron sputtering method is preferably performed at a vacuum level of 10. -3 ~10 -5 The process is carried out under a high vacuum of 1 Pa. The working gas is a mixture of oxygen and argon. In a preferred embodiment, the flow rate ratio of oxygen to argon is 10 sccm:70 sccm, and the sputtering pressure is controlled between 1 Pa and 1.5 Pa. Under these conditions, precise control of the oxygen flow rate can effectively prevent oxygen deficiency defects in the film during sputtering deposition, ensuring that the stoichiometric ratio of metal elements to oxygen in the film meets design requirements. Adjusting the working pressure within an appropriate range ensures sufficient density of the film material, thereby achieving superior electrochromic properties.
[0027] In one implementation of the present invention, the amorphous M x W y Mo zThe O3 cathode electrochromic layer is prepared by co-sputtering. Specifically, a metal M target (such as an Nb or Ti target), a metal W target, and a metal Mo target are simultaneously sputtered onto the same substrate surface. By independently adjusting the power supply of each target, the relative content of each metal element in the film can be precisely controlled. In a preferred embodiment, the power supply of the metal M target is 150 W to 250 W, more preferably 200 W to 250 W; the power supply of the metal W target is 20 W to 60 W; the power supply of the metal Mo target is 20 W to 120 W, more preferably 40 W to 120 W; and the sputtering time is 1 h.
[0028] In this invention, M x W y Mo z The proportions of each element in the O3 thin film are the decisive parameters for achieving a complete neutral color transition. Specifically, the value of x (the relative proportioning coefficient of element M) should be controlled within the range of 0.5 to 0.6, the value of y (the relative proportioning coefficient of element W) should be controlled within the range of 0.2 to 0.3, and the value of z (the relative proportioning coefficient of element Mo) should be controlled within the range of 0.1 to 0.2. Only when the three proportioning coefficients x, y, and z simultaneously fall within their respective value ranges can the material achieve uniform optical absorption characteristics across the entire visible light spectrum, thus exhibiting a complete neutral color transition effect from transparent to gray and then to black.
[0029] In one implementation of the present invention, the annealing temperature of the first annealing treatment is preferably 350℃~400℃, and the annealing time is 60 min~120 min. Using a relatively low annealing temperature of 350℃~400℃ ensures sufficient relaxation and stabilization of the film's microstructure while avoiding the transformation of the film from an amorphous to a crystalline state due to excessively high temperatures, thereby maintaining the isotropic ion transport channels and excellent electrochromic reversibility characteristic of the amorphous structure. x W y Mo z The thickness of the O3 cathode electrochromic layer is preferably controlled in the range of 300 nm to 400 nm to achieve the best balance between optical modulation amplitude and initial transmittance.
[0030] In one implementation of the present invention, the material of the transparent anodic ion storage layer is selected from Ce. a Ti b O film or M m V n O thin film (M is selected from at least one of Nb and Ta). When Ce is selected... a Ti bWhen O is used as the anolyte storage layer material, co-sputtering deposition is performed on the surface of an ITO glass substrate using a Ce target and a Ti target. The power supply for the Ce target is 120 W–200 W, and the power supply for the Ti target is 230 W–240 W, with a sputtering time of 4 h. The second annealing treatment is performed at a temperature of 300 °C–500 °C for 60 min–120 min. The resulting Ce... a Ti b In the O thin film, the preferred value of a is 0.4–0.8, and the preferred value of b is 0.2–0.6. When M is selected... m V n When O is used as the anolyte storage layer material, co-sputtering deposition is performed on the surface of an ITO glass substrate using a metal M target and a metal V target. The power supply for the metal M target is 30 W–45 W, and the power supply for the metal V target is 140 W–160 W, with a sputtering time of 1 h. The preferred annealing temperature for the second annealing treatment is 600 °C, and the annealing time is 120 min. The resulting M… m V n The preferred values for m and n in the O thin film are 0.4–0.6. The Ce obtained through the above preparation process... a Ti b O thin film and M m V n O films are all highly transparent and have no electrochromic response capability, so they will not change color with changes in applied voltage.
[0031] In one embodiment of the present invention, the transparent electrolyte is prepared by mixing a lithium salt solution with a UV-curable adhesive and stirring thoroughly under light-protected conditions. The lithium salt in the lithium salt solution is selected from at least one of lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium bis(oxaloyl)borate (LiBOB), lithium tetrafluoroborate (LiBF4), lithium difluorooxaloylborate (LiODFB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO2F3), and lithium tetrafluorooxaloyl phosphate (LiFOP). The solvent in the lithium salt solution is selected from at least one of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), ethyl carbonate, and diethyl carbonate (DEC).
[0032] Based on the above embodiments, the present invention also provides an electrochromic device with a neutral color change throughout the process, which is prepared by the preparation method of any of the above embodiments.
[0033] The following specific preparation examples will further explain the above-mentioned technical solutions provided by the present invention.
[0034] Example 1 Preparation of the cathode electrochromic layer: Commercial ITO was provided and cleaned to serve as the substrate. Nb, W, and Mo were co-sputtered onto the substrate surface using magnetron sputtering. During operation, the vacuum chamber of the magnetron sputtering equipment was evacuated to 10°C. -3 Under a vacuum of 1 Pa, the working gas was a mixture of oxygen and argon in a ratio of 10 sccm:70 sccm, at a pressure of 1 Pa. The power supply for the Nb target was set to 200 W, the W target to 40 W, and the Mo target to 80 W. Sputtering for 1 h yielded a 350 nm thick amorphous Nb-W-Mo-O film (chemical formula Nb). 0.55 W 0.3 Mo 0.15 O3). The resulting amorphous Nb 0.55 W 0.3 Mo 0.15 The O3 thin film was annealed in a muffle furnace. The temperature was first raised from room temperature to 400°C in air, then held for 60 minutes, and finally cooled to room temperature to obtain amorphous Nb. 0.55 W 0.3 Mo 0.15 O3 electrochromic film.
[0035] Fabrication of the anolyte storage layer: Commercial ITO was provided and cleaned to serve as the substrate. Ce and Ti were co-sputtered onto the substrate surface using magnetron sputtering. During operation, the vacuum chamber of the magnetron sputtering equipment was evacuated to 10°C. -3 Under a vacuum of 1 Pa, the working gas was a mixture of oxygen and argon in a ratio of 10 sccm:70 sccm, and the pressure was 1 Pa. The power supply to the Ce target was adjusted to 180 W and the power supply to the Ti target to 240 W. Amorphous Ce-Ti-O films (chemical formula Ce) were obtained after sputtering for 4 h. 0.7 Ti 0.3 O). The resulting amorphous Ce 0.7 Ti 0.3 The O film was annealed in a muffle furnace, first heated from room temperature to 500°C in air, then held for 120 min, and finally cooled to room temperature to obtain the cubic Ce phase. 0.7 Ti 0.3 O-ion storage layer.
[0036] Fabrication of the complete electrochromic device: The electrochromic thin film and the ion storage layer were assembled with the film surfaces facing each other and the electrodes facing opposite directions, separated by a spacer. A 1 mol / L lithium tetrafluoroborate (LiBF4) solution in propylene carbonate (PC) was used as the electrolyte, mixed with an acrylate-based UV-curable adhesive, and stirred in the dark to obtain a transparent electrolyte. The transparent electrolyte was injected into the device until the gaps were filled, and then cured and encapsulated under UV light to obtain an electrochromic device consisting of a cathode electrochromic layer that changes color throughout the series process, a transparent electrolyte, and an anode ion storage layer with no electrochromic activity.
[0037] The Nb prepared in Example 1 0.55 W 0.3 Mo 0.15 O3 electrochromic film and Ce 0.7 Ti 0.3 The O-ion storage layers were placed in glove boxes with water and oxygen content both less than 0.01%, and electrochemical tests were performed using a three-electrode system: the electrolyte was a 1 mol / L LiBF4-PC solution, the counter electrode and reference electrode were both lithium foil, and the working electrode was the Nb2 prepared in Example 1. 0.55 W 0.3 Mo 0.15 O3 electrochromic film and Ce 0.7 Ti 0.3 The O-ion storage layer was subjected to cyclic voltammetry (CV) tests at a scan rate of 5 mV / s within voltage windows of 1.8 V to 4 V and 1.5 V to 4 V, respectively. At the same time, the changes in optical transmittance in the visible light band (400 nm to 800 nm) during the electrochromic process of the thin film were recorded in situ.
[0038] Figure 1 For Nb 0.55 W 0.3 Mo 0.15 The optical transmittance of the O3 electrochromic thin film in the visible light band under different voltages during the electrochromic process shows that the transmittance of the film in the entire visible light band maintains an extremely gradual downward trend during the change from the initial state to the colored state. The maximum modulation amplitude of the film at a wavelength of 550 nm reaches 66.61%, which corresponds to the neutral color evolution from transparent to gray and finally to black.
[0039] Figure 2 For Ce 0.7 Ti 0.3 The optical transmittance spectra of the O-ion storage layer in the transparent state and after applying a bias voltage are shown. The results indicate that the optical transmittance of the film remains almost unchanged during the applied voltage process, and no visible color change occurs throughout the electrochemical process. It maintains a highly transparent state and does not exhibit electrochromic activity, thus it can interact with Nb. 0.55 W0.3 Mo 0.15 Devices were fabricated by pairing O3 electrochromic thin films.
[0040] The electrochromic device prepared in Example 1 was placed in a glove box with a water and oxygen content of less than 0.01%. Cyclic voltammetry (CV) tests were performed at a scan rate of 5 mV / s within a voltage window of -2.5 V to 2.5 V. Simultaneously, the changes in optical transmittance in the visible light band (400 nm to 800 nm) during the electrochromic process were recorded in situ. Next, a constant voltage cyclic test was performed on the device: a voltage of -2.5 V was applied for 30 s, at which point the device began to color; a voltage of 2.5 V was applied for 25 s, at which point the device began to fade. Simultaneously, the changes in optical transmittance in the single-wavelength spectrum (at 550 nm) during the electrochromic process were recorded in situ.
[0041] Figure 3 For assembling Nb 0.55 W 0.3 Mo 0.15 O3 electrochromic film and Ce 0.7 Ti 0.3 The optical transmittance of the device obtained by the O-ion storage layer under different voltages in the visible light band during the electrochromic process can be seen as follows: during the transition of the device from the initial state to the colored state, the transmittance in the entire visible light band shows a gradual decreasing trend, and the maximum modulation amplitude of 40% is achieved at the characteristic wavelength of 550 nm, which corresponds to the gradient visual effect from transparent to gray and finally to black, realizing the neutral color evolution of the entire electrochromic process.
[0042] Figure 4 This image shows the change in single-wavelength optical transmittance of the electrochromic device at 550 nm under constant voltage cycling tests. The results indicate that after 200 cycles, both the bleached and colored states of the device maintain good stability without significant degradation. This demonstrates that by combining an electrochromic film capable of achieving full-process neutral color evolution with an ion storage layer lacking electrochromic activity, both the structural and performance stability of the complete electrochromic device are achieved, and the device maintains its full-process neutral color transition throughout the color-changing process.
[0043] Based on the optical transmittance changes in the visible light band under different voltages in Example 1, Table 1 lists the CIE L values of the device prepared in Example 1 under different voltages. a b Color coordinate values, where L Represents brightness, a Indicates the red-green bias of a color, b This indicates the yellow-blue bias of the color. It can be seen that throughout the entire electrochromic process, the device's a... and b The absolute values of both are close to 0, indicating that there is no obvious tendency for color change, presenting an excellent neutral color effect. Combined with L... As can be seen from the changing pattern of the values, in Example 1, there is almost no change in chromaticity during the color change process, only a dynamic change in brightness, achieving a continuous transformation from transparent to gray and then to black.
[0044] Table 1: CIE L values of the thin film prepared in Example 1 at different voltages a b Color coordinate values.
[0045]
[0046] Figure 5 The three-dimensional CIE L model of the device in Example 1 during the color-changing process is shown. a b The color coordinate variation graph shows that the perpendicular lines to the color coordinate points corresponding to different voltages almost coincide, and the perpendicular lines are perpendicular to a. b The intersection points of the surfaces all approach a. =0 and b The central white dot corresponding to the value of 0 indicates that the device only changes in brightness without changing chromaticity during the color-changing process, thus realizing the complete neutral color evolution of the electrochromic device throughout the entire process.
[0047] Example 2 The only difference between this embodiment and Embodiment 1 is that the M element in the cathode electrochromic layer is replaced by Ti instead of Nb, while the other conditions remain unchanged.
[0048] Fabrication of the cathode electrochromic layer: The same commercial ITO substrate as in Example 1 was used. Ti, W, and Mo were co-sputtered onto the substrate surface using magnetron sputtering, with a vacuum level of 10⁻⁶ ppm in the vacuum chamber. -4 The flow rate ratio of oxygen to argon was 10 sccm:70 sccm, and the sputtering pressure was 1 Pa. The power supply for the Ti target was adjusted to 180 W, the W target to 40 W, and the Mo target to 80 W. Sputtering was performed for 1 h, yielding an amorphous Ti-W-Mo-O film with a thickness of 350 nm and the chemical formula Ti. 0.55 W 0.3 Mo 0.15 O3. The obtained film was placed in a muffle furnace and heated from room temperature to 400°C in air, held at that temperature for 60 min, and then naturally cooled to room temperature to obtain amorphous Ti. 0.55 W 0.3 Mo 0.15 O3 cathode electrochromic thin film.
[0049] Preparation of the anodic ion storage layer: Same as in Example 1, using Ce 0.7 Ti 0.3 O-ion storage layer.
[0050] Fabrication of a complete electrochromic device: Ti 0.55 W 0.3 Mo 0.15 O3 electrochromic film and Ce 0.7 Ti 0.3 The O-ion storage layer was assembled, injected with a transparent electrolyte, and encapsulated under UV curing in the same manner as in Example 1 to obtain an electrochromic device.
[0051] The thin films and devices prepared in Example 2 were characterized using the same electrochemical testing conditions and in-situ spectroscopic recording methods as in Example 1. The test results show that Ti... 0.55 W 0.3 Mo 0.15 During the transition from the initial state to the colored state, the transmittance of the O3 thin film exhibits a uniform and gradual decreasing trend across the entire visible light spectrum (400 nm–800 nm), with an optical modulation amplitude exceeding 50% at 550 nm, corresponding to a neutral color evolution effect from transparent to gray and then to black. The assembled complete device also exhibits uniform optical modulation across the entire visible light spectrum within a voltage window of -2.5 V to 2.5 V, with a modulation amplitude exceeding 30% at the characteristic wavelength of 550 nm, corresponding to the a... and b The absolute value remained close to 0 throughout the color-changing process, verifying that the technical solution of this invention can also achieve a neutral color change effect throughout the entire process when M=Ti. After 200 constant voltage coloring-fading cycles, the device performance remained stable without significant degradation.
[0052] The results of Example 2 fully demonstrate that the choice of M element as defined in this invention is not limited to Nb; Ti can also be used as an M element to construct M. x W y Mo z The O3 cathode electrochromic layer achieves neutral color effects throughout the process.
[0053] Example 3 The only difference between this embodiment and Embodiment 1 is that the anolyte storage layer is made of Ce. 0.7 Ti 0.3 O is replaced with Ta 0.5 V 0.5 O(M) m V n O thin film, where M=Ta), with other conditions remaining unchanged.
[0054] Preparation of the cathode electrochromic layer: Same as in Example 1, using amorphous Nb 0.55 W 0.3 Mo 0.15 O3 electrochromic film.
[0055] Fabrication of the anolyte storage layer: Commercial ITO was provided and cleaned to serve as the substrate. Ta and V metals were co-sputtered onto the substrate surface using magnetron sputtering. During operation, the vacuum chamber of the magnetron sputtering equipment was evacuated to 10°C. -5 Under a vacuum of 1 Pa, the working gas was a mixture of oxygen and argon in a ratio of 10 sccm:70 sccm, at a pressure of 1 Pa. The power supply to the Ta target was adjusted to 40 W and the power supply to the V target to 150 W. Amorphous Ta-VO films were obtained after sputtering for 1 h. The resulting films were placed in a muffle furnace and heated from room temperature to 600 °C in air, held at that temperature for 120 min, and then naturally cooled to room temperature to obtain Ta with a crystalline structure. 0.5 V 0.5 O-ion storage layer.
[0056] Ta 0.5 V 0.5 The O-ion storage layer was placed in a glove box with water and oxygen content both less than 0.01%. Electrochemical tests were performed using the same three-electrode system as in Example 1, with cyclic voltammetry (CV) tests conducted at a scan rate of 5 mV / s within a voltage window of 1.5 V to 4 V. Simultaneously, the optical transmittance changes of the film in the visible light band (400 nm to 800 nm) were recorded in situ. The test results show that throughout the entire voltage application process, Ta... 0.5 V 0.5 The optical transmittance of the O film remains almost unchanged, maintaining a consistently high level of transparency, confirming its lack of electrochromic activity and suitability for use with Nb. 0.55 W 0.3 Mo 0.15 O3 cathode electrochromic thin films are paired to construct devices.
[0057] Fabrication of a complete electrochromic device: using amorphous Nb 0.55 W 0.3 Mo 0.15 O3 cathode electrochromic film and Ta 0.5 V 0.5 The O-ion storage layer was assembled, injected with a transparent electrolyte, and encapsulated under UV curing in the same manner as in Example 1.
[0058] Electrochemical and optical characterization of the device in Example 3 was performed using the same testing methods as in Example 1. The test results show that during the transition from the initial state to the colored state, the transmittance across the entire visible light spectrum exhibits a gradual decreasing trend, with an optical modulation amplitude exceeding 35% at the characteristic wavelength of 550 nm. This corresponds to a gradual visual effect from transparent to gray and finally to black, achieving a neutral color evolution throughout the entire electrochromic process. (CIE L) a b Color coordinate analysis shows that the device is used throughout the color-changing process. and b The absolute value of the chromaticity always approaches 0, with only continuous changes in brightness without altering the chromaticity. After 200 constant voltage cycles, the device maintained good stability in both the bleached and colored states.
[0059] The results of Example 3 fully demonstrate that M m V n O thin film (M=Ta) can serve as a transparent anodic ion storage layer without electrochromic activity, and with M x W y Mo z O3 cathode electrochromic layers are paired to construct a neutral color electrochromic device throughout the process.
[0060] Example 4 The only difference between this embodiment and Embodiment 1 is that the cathode electrochromic layer M... x W y Mo z The elemental proportions of O3 were adjusted from the middle value (x=0.55, y=0.3, z=0.15) to the high end of the composition range (x=0.6, y=0.3, z=0.1), while the other conditions remained unchanged.
[0061] Preparation of the cathode electrochromic layer: The same commercial ITO substrate and magnetron sputtering process conditions as in Example 1 were used. The power supply for the Nb target was adjusted to 250 W, the W target to 40 W, and the Mo target to 20 W. Sputtering was performed for 1 h to obtain an amorphous Nb-W-Mo-O film with a thickness of 350 nm. The chemical formula is Nb 0.6 W 0.3 Mo 0.1 O3. The obtained film was placed in a muffle furnace and heated from room temperature to 400°C in air, held at that temperature for 60 min, and then naturally cooled to room temperature to obtain amorphous Nb. 0.6 W 0.3 Mo 0.1 O3 cathode electrochromic thin film.
[0062] Preparation of the anodic ion storage layer: Same as in Example 1, using Ce0.7 Ti 0.3 O-ion storage layer.
[0063] Fabrication of a complete electrochromic device: using amorphous Nb 0.6 W 0.3 Mo 0.1 O3 cathode electrochromic thin film and Ce 0.7 Ti 0.3 The O-ion storage layer was assembled, injected with a transparent electrolyte, and encapsulated under UV curing in the same manner as in Example 1.
[0064] The thin films and devices prepared in Example 4 were characterized using the same electrochemical testing conditions and in-situ spectroscopic recording methods as in Example 1. The test results showed that Nb 0.6 W 0.3 Mo 0.1 During the transition from the initial state to the colored state, the transmittance of the O3 thin film decreases gradually across the entire visible light spectrum (400 nm–800 nm), with an optical modulation amplitude exceeding 60% at 550 nm, corresponding to a complete neutral color evolution from transparent to gray and then to black. The optical modulation results of the assembled complete device within a voltage window of -2.5 V to 2.5 V also confirm the complete neutral color transition characteristics at the device level, with a modulation amplitude exceeding 35% at 550 nm. CIE color coordinate analysis shows that throughout the electrochromic process, a… and b The value remained consistently close to 0, and the color change process was only manifested as L. The value (brightness) changes continuously. A 200-cycle stability test shows that the device performance remains good.
[0065] Comparative Example 1 Preparation of the electrochromic layer: Commercial ITO was provided and cleaned to serve as the substrate. Nb, W, and Mo were co-sputtered onto the substrate surface using magnetron sputtering. During operation, the vacuum chamber of the magnetron sputtering equipment was evacuated to 10°C. -3 Under a vacuum of 1 Pa, the working gas was a mixture of oxygen and argon in a ratio of 10 sccm:70 sccm, at a pressure of 1 Pa. The power supply for the Nb target was set to 200 W, the W target to 40 W, and the Mo target to 80 W. Sputtering for 1 h yielded a 350 nm thick amorphous Nb-W-Mo-O film (chemical formula Nb). 0.55 W 0.3 Mo 0.15 O3).
[0066] The thin film prepared in this comparative example was not annealed, resulting in poor cycling stability, and the corresponding electrochromic device could not maintain good cycling stability. Compared with Example 1, Comparative Example 1 demonstrates that annealing treatment significantly improves the cycling stability of the film. x W y Mo z The cycling stability of O3 thin films plays a crucial role. While unannealed films can achieve a neutral color effect, the large internal stress and numerous defect states in the sputtered state cause irreversible evolution of the film's microstructure during repeated lithium-ion insertion and extraction, leading to rapid degradation of cycling performance. Annealing at 350℃–400℃ effectively releases the internal stress, allows for moderate short-range ordered rearrangement of atoms within the amorphous framework, and significantly reduces the defect state density. This results in excellent cycling stability while maintaining the ability to evolve neutral color throughout the process.
[0067] Comparative Example 2 Preparation of the electrochromic layer: Commercial ITO was provided and cleaned to serve as the substrate. Nb, W, and Mo were co-sputtered onto the substrate surface using magnetron sputtering. During operation, the vacuum chamber of the magnetron sputtering equipment was evacuated to 10°C. -3 Under a vacuum of 1 Pa, the working gas was a mixture of oxygen and argon in a ratio of 10 sccm:70 sccm, at a pressure of 1 Pa. The power supply for the Nb target was set to 200 W, the W target to 50 W, and the Mo target to 100 W. Sputtering for 1 h yielded a 350 nm thick amorphous Nb-W-Mo-O film (chemical formula Nb). 0.3 W 0.35 Mo 0.35 O3). The resulting amorphous Nb 0.3 W 0.35 Mo 0.35 The O3 thin film was annealed in a muffle furnace. The temperature was first raised from room temperature to 400°C in air, then held for 60 minutes, and finally cooled to room temperature to obtain amorphous Nb. 0.3 W 0.35 Mo 0.35 O3 electrochromic film.
[0068] The thin film prepared in this comparative example exhibits a brownish-yellow color and does not have a neutral color evolution effect throughout the process. The corresponding electrochromic device also cannot achieve a neutral color evolution throughout the process.
[0069] Comparative Example 3 Thin film preparation process: Commercial ITO was provided and cleaned to serve as the substrate. Nb, W, and Mo were co-sputtered onto the substrate surface using magnetron sputtering. During operation, the vacuum chamber of the magnetron sputtering equipment was evacuated to 10°C. -5Under a vacuum of 1 Pa, the working gas was a mixture of oxygen and argon in a ratio of 10 sccm:70 sccm, and the pressure was 1 Pa. The power supply for the Nb target was set to 200 W, the W target to 60 W, and the Mo target to 50 W. Sputtering for 1 h yielded a 350 nm thick amorphous Nb-W-Mo-O film (chemical formula Nb). 0.35 W 0.55 Mo 0.1 O3). The resulting amorphous Nb 0.35 W 0.55 Mo 0.1 The O3 thin film was annealed in a muffle furnace. The temperature was first raised from room temperature to 400°C in air, then held for 60 minutes, and finally cooled to room temperature to obtain amorphous Nb. 0.35 W 0.55 Mo 0.1 O3 electrochromic film.
[0070] The thin film prepared in this comparative example exhibits a blue color state and does not have a neutral color evolution effect throughout the process. The corresponding electrochromic device also cannot achieve a neutral color evolution throughout the process.
[0071] The results of Comparative Example 2 and Comparative Example 3 together show that M x W y Mo z The proportions of each element in the O3 thin film (the values of x, y, and z) are key parameters for achieving a neutral color transition throughout the process. In Comparative Example 2, when the contents of W and Mo reach y=0.35 and z=0.35 respectively (exceeding the range of y=0.2~0.3 and z=0.1~0.2 defined in this invention), the film exhibits a brownish-yellow color, losing its neutral color effect. In Comparative Example 3, when the W content is as high as y=0.55 and the Nb content is only x=0.35 (exceeding the range of x=0.5~0.6 and y=0.2~0.3 defined in this invention), the film exhibits a blue color, also lacking the ability to evolve into a neutral color throughout the process.
[0072] Based on the experimental results of Examples 1 and 4, and Comparative Examples 2 and 3, the following conclusion can be drawn: Only when M x W y Mo zWhen the proportions of x (M element ratio) in the O3 thin film are within the ranges of 0.5–0.6, y (W element ratio) within the ranges of 0.2–0.3, and z (Mo element ratio) within the ranges of 0.1–0.2, the absorption contributions of the three elements across the entire visible light spectrum achieve optimal balance. This results in a uniform and smooth full-spectrum optical modulation characteristic throughout the coloring process, exhibiting a continuous neutral color transition from transparent to gray to black. When the proportion of any element deviates from the above ranges, the material exhibits biased absorption in specific wavelengths (excessive W content leads to enhanced absorption in the blue light region, resulting in a blue hue; an imbalance in the W-Mo ratio leads to abnormal absorption in the long-wavelength region, resulting in a brownish-yellow hue). The color state shows a color bias, thus losing its neutral color characteristics and the ability to evolve neutrally throughout the entire process. This discovery provides a basis for determining the M element in this invention. x W y Mo z The compositional range of O3 provided the basis for the experiments.
[0073] In summary, this invention provides a method for fabricating an electrochromic device with a neutral color change throughout the entire process, by dynamically controlling the amorphous cathode M x W y Mo z The elemental ratio in O3 alters the optical absorption capacity of the layer across different wavelengths, resulting in a cathode electrochromic film capable of undergoing a complete neutral color evolution. This film can then be combined with a transparent ion storage layer (such as Ce) that lacks electrochromic activity. a Ti b O or the general formula is M m V n By combining an electrochromic active ion storage layer (O) with an electrochromic layer without electrochromic properties, the resulting electrochromic device possesses excellent cycling stability, optical modulation, and the ability to evolve neutral colors throughout the process. This meets the human eye's comfort requirements for neutral colors, making it a promising candidate for applications in smart windows, wearable devices, and other fields, thus expanding the application prospects of electrochromic technology in real life.
[0074] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.
Claims
1. A method for preparing an electrochromic device with a neutral color change throughout the entire process, characterized in that, Includes the following steps: M was obtained by co-sputtering metals M, W, and Mo on the surface of the first ITO glass using magnetron sputtering. x W y Mo z O3 thin film, wherein M is selected from at least one of Nb and Ti; For the M x W y Mo z The O3 thin film underwent a first annealing treatment to obtain amorphous M. x W y Mo z O3 cathode electrochromic layer; Metal oxides were co-sputtered onto the surface of a second ITO glass using magnetron sputtering, and the resulting film was subjected to a second annealing treatment to obtain a transparent anodic ion storage layer without electrochromic activity. The amorphous M x W y Mo z The O3 cathode electrochromic layer and the transparent anode ion storage layer are assembled with their thin film surfaces facing each other and their electrodes facing opposite directions, separated by a spacer. Injecting a transparent electrolyte into amorphous M x W y Mo z The gap between the O3 cathode electrochromic layer and the transparent anode ion storage layer is encapsulated to obtain the electrochromic device.
2. The method for preparing the electrochromic device according to claim 1, characterized in that, The vacuum level of the vacuum chamber in the magnetron sputtering method is 10. -3 ~10 -5 Pa, the working gas is a mixture of oxygen and argon.
3. The method for preparing the electrochromic device according to claim 1, characterized in that, Amorphous M was prepared by magnetron sputtering. x W y Mo z O3 cathode electrochromic layer, wherein the power supply of the metal M target is 150 W to 250 W, the power supply of the metal W target is 20 W to 60 W, and the power supply of the metal Mo target is 20 W to 120 W. Preferably, the annealing temperature of the first annealing treatment is 350℃~400℃, and the annealing time is 60 min~120 min.
4. The method for preparing the electrochromic device according to claim 1, characterized in that, The M x W y Mo z In the O3 thin film, x takes values of 0.5~0.6, y takes values of 0.2~0.3, and z takes values of 0.1~0.2; Preferably, the M x W y Mo z The thickness of the O3 thin film electrochromic film is 300~400nm.
5. The method for preparing the electrochromic device according to claim 1, characterized in that, The material of the transparent anodic ion storage layer is Ce. a Ti b O film or M m V n O thin film; wherein M is selected from at least one of Nb and Ta.
6. The method for preparing the electrochromic device according to claim 5, characterized in that, When the transparent anodic ion storage layer is Ce a Ti b When sputtering the O thin film, a Ce metal target and a Ti metal target are used for co-sputtering on the surface of the second ITO glass substrate; wherein, the power supply of the Ce metal target is 120 W to 200 W, and the power supply of the Ti metal target is 230 W to 240 W; the annealing temperature of the annealing treatment is 300℃ to 500℃, and the annealing time is 60 min to 120 min. Preferably, the Ce a Ti b The a value in the O thin film is 0.4~0.8 and the b value is 0.2~0.
6.
7. The method for preparing the electrochromic device according to claim 5, characterized in that, When the transparent anodic ion storage layer is M m V n When sputtering the ITO thin film, a metal M target and a metal V target are used to co-sputter the film on the surface of the ITO glass substrate; wherein the power of the metal M target is 30 W to 45 W and the power of the metal V target is 140 W to 160 W; the annealing temperature of the annealing treatment is 580-620℃ and the annealing time is 100-140 min. Preferably, the M m V n The m value in the O thin film is 0.4~0.6, and the n value is 0.4~0.
6.
8. The method for preparing the electrochromic device according to claim 1, characterized in that, The transparent electrolyte is obtained by mixing a lithium salt solution with a UV-curable adhesive and stirring in the dark. The lithium salt in the lithium salt solution includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium bis(oxaloyl)borate, lithium tetrafluoroborate, lithium difluorooxaloylborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, and lithium tetrafluorooxaloyl phosphate.
9. The method for preparing the electrochromic device according to claim 8, characterized in that, The solvent in the lithium salt solution includes at least one of propylene carbonate, ethylene carbonate, dimethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, ethyl carbonate, and diethyl carbonate.
10. An electrochromic device with a neutral color change throughout the entire process, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 9.